Surface and interface engineering for highly efficient Cu2ZnSnSe4thin-film solar cellsvia in situformed ZnSe nanoparticles - Yoo, Hyesun; Park, Jongsung; Suryawanshi, Mahesh P.; Lee, Jiwon; Kim, Jun Ho; Eom, Kiryung; Seo, Hyungtak; Jung, Hyo Rim; Kim, Dong Myeong; Shin, Seung Wook; Kim, Jin Hyeok (Journal of Materials Chemistry A, 2021)
Kesterite surface properties and band alignment behavior at an absorber/buffer interface are key issues for highly efficient kesterite solar cell devices. Herein, we report new insights into surface and interface engineering and favorable band alignment of Cu2ZnSnSe4(CZTSe)/CdS buffer in solar cellsvia in situformed ZnSe nanoparticles (NPs) on the CZTSe surface. The device characteristics and junction qualities of the CZTSe solar cells within situformed ZnSe NPs are improved even though they have similar bulk properties to CZTSe thin films. X-ray photoelectron spectroscopy (XPS) characterization revealed a favorable conduction band offset (CBO, +0.26 eV) for CZTSe/ZnSe NPs/CdS compared to that for CZTSe/CdS (+0.01 eV) and CZTSe/ZnSe layer/CdS (+0.976 eV), respectively. In this regard, we also postulated a formation mechanism forin situformed ZnSe NPs on the CZTSe surfaceviaannealing of metallic precursors with different stacking orders. This work offers a simple and source-free interface engineering strategy usingin situformed ZnSe NPs (secondary phase) on the CZTSe surface to further improve the performance of kesterite solar cell devices.
Keywords: Conduction band offset; Device characteristics; Formation mechanism; Metallic precursor; Secondary phase; Solar cell devices; Surface and interfaces; ZnSe nanoparticles